Comparison of frequency of diagnosis, induction of labour and caesarean section in patients with isolated oligohydramnios diagnosed by amniotic fluid index versus single deepest vertical pocket - Rehman, Saleema; Bilqis, Humaira; Rizwan, Humera; Akram, Ayesha; Kousar, Shermeen; Irshad, Samina (Journal of Rawalpindi Medical College, 2022)
Objective: To compare the frequency of diagnosis, induction of labour and caesarean section in patients with isolated oligohydramnios diagnosed by amniotic fluid index versus single deepest vertical pocket. Study design: Randomized controlled trial Place and duration of study: Department of Obstetrics and Gynecology, Holy Family hospital, Rawalpindi from March 2020 to August 2020. Materials & Methods: A total of 110 (55 in each group), 18 to 35 years of age of parity <5 were included. Group A females were evaluated by using AFI and group B females were evaluated by using SDVP. Patients were managed according to standard protocol practiced in the department. Caesarean section was performed in case of fetal distress, in presence of meconium stained liquor or in case of failure to progress of labour. Results: In my study, oligohydramnios was recorded in 19/55 (34.50%) in group A (amniotic fluid index) versus 11/55 (20.0%) in group B (single deepest vertical pocket) (p-value = 0.086). Similarly induction of labour was recorded in 19/55 (34.50%) in group A (amniotic fluid index) versus 11/55 (20.0%) in group B (single deepest vertical pocket) (p-value = 0.086) and caesarean section was recorded in 16/55 (29.09%) in group A (amniotic fluid index) versus 07/55 (12.73%) in group B (single deepest vertical pocket) (p-value = 0.035). Conclusion: This study concluded that frequency of diagnosis, induction of labour and caesarean section in patients with isolated oligohydramnios diagnosed by amniotic fluid index is higher as compared to single deepest vertical pocket. Keywords: Oligohydramnios, Amniotic fluid index, Single deepest vertical pocket